MENINGKATKAN KETERAMPILAN KOLABORASI DAN KREATIVITAS SISWA MELALUI MODEL PBL, RME, NHT DAN MEDIA BUKU SAKU PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN MALUTU HSS - Widi Kurniyati; Tika Puspita Widya Rini (STKIP Subang, 2025)
The low levels of teacher and student activity, collaboration and creativity skills, as well as student learning outcomes in Grade IV became the central issues in this study conducted at SDN Malutu. These problems were due to the limited use of interactive learning models that encourage student engagement. To address this, the PBL, RME, and NHT models were implemented, supported by the use of Pocket Book media. This was a Classroom Action Research (CAR) carried out over four sessions in Grade IV of SDN Malutu during the 2024/2025 academic year, involving 13 students. Data collected included qualitative data from observations of teacher and student activities, collaboration and creativity skills, and quantitative data from students' written test results. The findings revealed progressive improvements from session 1 to session 4: teacher activity increased from a score of 24 to 28, student activity from 46% to 100%, collaboration skills from 31% to 92%, and creativity from 23% to 92%. Learning outcomes also improved in the cognitive aspect (from 38% to 100%), affective aspect (from 46% to 85%), and psychomotor aspect (from 38% to 92%). In conclusion, the use of these varied models and media proved effective in enhancing teacher and student activity, collaboration skills, creativity, and student learning outcomes.